Analisis Potensi Penerapan Target Costing sebagai Strategi Pengendalian Biaya Produksi pada PT Cisarua Mountain Dairy Tbk: Analysis of the Potential Implementation of Target Costing as a Production Cost Control Strategy at PT Cisarua Mountain Dairy Tbk - Louisa Pernanda; Vina fatkhiyatu zahroh; Riska Amelia; Nabila Annasthasya; Indri Rahmawati (Jurnal Manajemen dan Akuntansi Cakrawarti, 2026)
This study aims to analyze the potential application of the Target Costing method as a production cost control strategy at PT Cisarua Mountain Dairy Tbk based on the company's 2025 financial statements. The research employed a descriptive quantitative approach using secondary data obtained from the company's annual report. The analysis was conducted by comparing the Traditional Costing and Target Costing approaches to evaluate production cost efficiency and identify opportunities for improving profitability. The results indicate that the company recorded net sales of IDR 10.724 trillion, cost of goods sold of IDR 5.871 trillion, gross profit of IDR 4.853 trillion, and net income of IDR 2.033 trillion. The cost of goods sold accounted for 54.75% of net sales, while the gross profit margin reached 45.25%, indicating a high level of production cost efficiency. The Target Costing simulation produced a maximum allowable cost of IDR 8.691 trillion, which was higher than the actual production cost, resulting in a potential cost efficiency of IDR 2.820 trillion. These findings demonstrate that the company has effectively controlled its production costs. Furthermore, a more systematic implementation of Target Costing has the potential to enhance operational efficiency, strengthen competitiveness, and support sustainable profitability.